The effects of resistance to trypanocidal drugs on trypanosome transmission - McDermott, John J.; Coleman, P.G.; Eisler, M.C.; Peregrine, A.S. (International Society for Veterinary Epidemiology and Economics, 2000)
Tsetse-transmitted trypanosomosis affects cattle production over approximately 10 million km2 of Africa. In these areas, trypanocidal drugs, both prophylactic and curative, are the most widely used methods of trypanosomosis control. However, resistance of trypanosomes to the 3 trypanocidal drugs used in cattle (salts of isometamidium, diminsine and homidium) has been widely Reported and is considered to be increasing. The worst problems of trypanocidal drag resistance appear to occur where cattle are frequently treated in response to high trypanosome challenge. New trypanocides are unlikely to be developed because of low expected commercial retains . Thus, an important consideration in all trypanosomosis control programmes is how to either preserve the efficacy of trypanocides or, where widespread resistance exists, minimize its effects. In this paper, we explore the effects of drug resistance on trypanosome transmission under 3 important field scenarios.